1986
DOI: 10.3181/00379727-183-1-rc2
|View full text |Cite
|
Sign up to set email alerts
|

Female Rats are Protected against the Fructose Induced Mortality of Copper Deficiency

Abstract: Experiments were conducted in copper deficient male and female rats fed diets containing fructose or starch in order to determine whether the same type of interaction between copper status and dietary carbohydrate found in male rats also occurs in the female rat. Mortality occurred only in the male rats fed the fructose diet deficient in copper with 40% of the animals dying during the 8 week study. Only anemia, hypercholesterolemia, increased BUN, heart hypertrophy and reduced body weight were observed in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2
2

Year Published

1988
1988
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 15 publications
2
25
2
2
Order By: Relevance
“…This finding is in agreement with past studies in which male rats fed either starch or fructose exhibited similar concentrations of Cu in numerous tissues, and yet only Cu-deficient rats fed fructose exhibited severe pathol ogies [1][2][3]. In addition, female and male rats that were fed the fructose diet deficient in Cu were similarly Cu deficient, but only males developed numerous pathologies; they died of the deficiency, while females survived [20]. Thus, other factors in addition to Cu participate in the production of the pathologies associated with Cu defi ciency.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in agreement with past studies in which male rats fed either starch or fructose exhibited similar concentrations of Cu in numerous tissues, and yet only Cu-deficient rats fed fructose exhibited severe pathol ogies [1][2][3]. In addition, female and male rats that were fed the fructose diet deficient in Cu were similarly Cu deficient, but only males developed numerous pathologies; they died of the deficiency, while females survived [20]. Thus, other factors in addition to Cu participate in the production of the pathologies associated with Cu defi ciency.…”
Section: Discussionsupporting
confidence: 93%
“…When deaths are sudden, deficient males are more susceptible (165), when deaths occur with thrombosis, deficient females are more susceptible (166). Lerner et al (167) confirmed the observation of Spiekerman et al (36) that sudden death in ischemic heart disease is more common in men.…”
Section: Ischemic Heart Disease Resembles Copper Deficiencysupporting
confidence: 74%
“…It was shown that female rats are protected against the fructose induced mortality of copper deficiency [4]. An other study reports that male rats fed fructose based, low copper diet show 100% mortality, cardiac hypertrophy and anemia under conditions where female rats fed the same diet remained unaffected [14].…”
Section: Resultsmentioning
confidence: 99%